2017
DOI: 10.4103/jrms.jrms_614_16
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotic supplement on hemoglobin in chronic renal failure patients under hemodialysis: A randomized clinical trial

Abstract: Background:Chronic inflammation is one of the causes of anemia in chronic renal failure patients under hemodialysis. Probiotics probably establish a balance between pro- and anti-inflammatory cytokines. The study was conducted to determine the effects of probiotic supplementation on hemoglobin (Hb) in hemodialysis patients.Materials and Methods:A parallel clinical trial was conducted in which patients were randomly allocated into two groups. The intervention group (n = 18) was given a 500 mg probiotic suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 29 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Some studies related this to the stimulation of the haematopoietic organs [ 69 ] and also to the indirect effect of some lactic acid bacteria, including Lactobacilli , by increasing the bioavailability of dietary iron through several mechanisms such as the reduction of intestinal pH [ 70 ]. In agreement with our findings, the use of Lactobacillus rhamnosus for a period of three months in combination with other probiotic strains ( Lactobacillus acidophilus , Lactobacillus casei , Lactobacillus bulgaricus , Bifidobacterium breve , Bifidobacterium longum , and Streptococcus thermophilus ), increased the level of haemoglobin remarkably [ 71 ]. In contrast, other studies have noted that the treatment with Pediococcus acidilactici at a concentration of 10 9 cfu/g does not affect the erythrogram of broilers [ 72 ].…”
Section: Resultssupporting
confidence: 90%
“…Some studies related this to the stimulation of the haematopoietic organs [ 69 ] and also to the indirect effect of some lactic acid bacteria, including Lactobacilli , by increasing the bioavailability of dietary iron through several mechanisms such as the reduction of intestinal pH [ 70 ]. In agreement with our findings, the use of Lactobacillus rhamnosus for a period of three months in combination with other probiotic strains ( Lactobacillus acidophilus , Lactobacillus casei , Lactobacillus bulgaricus , Bifidobacterium breve , Bifidobacterium longum , and Streptococcus thermophilus ), increased the level of haemoglobin remarkably [ 71 ]. In contrast, other studies have noted that the treatment with Pediococcus acidilactici at a concentration of 10 9 cfu/g does not affect the erythrogram of broilers [ 72 ].…”
Section: Resultssupporting
confidence: 90%
“…In another trial, however, a 12-week supplementation of hemodialysis patients with a multi-strain probiotic preparation did not affect the hemoglobin status; the inefficacy of probiotics in the improvement of inflammation was considered responsible for this result. [ 50 ] Probiotic administration also showed no positive effect on Hb level in HIV patients and healthy elders in the other trials. [ 52 53 ]…”
Section: Discussionmentioning
confidence: 99%
“…Anemia and low Hb level associated with declining renal function is another common complication of CKD that may negatively affect the quality of life. [ 50 ] The mean Hb level showed a significant increasing trend in patients supplemented with probiotic or synbiotic formulations, while Hb level variability was observed in the placebo group. Considering the potential role of inflammation in CKD-anemia and Hb fluctuation,[ 47 48 ] the anti-inflammatory activity of probiotic strains observed in our previous studies[ 23 40 ] may explain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of chronic renal failure toward end-stage renal disease is increasing. [1] It is reported that the rate of mortality in chronic hemodialysis is 7–8 times greater than the general population. [2]…”
Section: Introductionmentioning
confidence: 99%